Clinical Experience and Recent Advances in the Development of Listeria-Based Tumor Immunotherapies - Oladejo, Mariam; Paterson, Yvonne; Wood, Laurence M. (Frontiers in Immunology, 2021)
The promise of tumor immunotherapy to significantly improve survival in patients who are refractory to traditional therapies is now being realized. While immune checkpoint inhibitors that target PD-1 and CTLA-4 are leading the charge in clinical efficacy, there are a number of other promising tumor immunotherapies in advanced development such as Listeria-based vaccines. Due to its unique life cycle and ability to induce robust CTL responses, attenuated strains of Listeria monocytogenes (Lm) have been utilized as vaccine vectors targeting both infectious disease and cancer. In fact, preclinical studies in a multitude of cancer types have found Listeria-based vaccines to be highly effective at activating anti-tumor immunity and eradicating tumors. Several clinical trials have now recently reported their results, demonstrating promising efficacy against some cancers, and unique challenges. Development of the Lm-based immunotherapies continues with discovery of improved methods of attenuation, novel uses, and more effective combinatorial regimens. In this review, we provide a brief background of Listeria monocytogenes as a vaccine vector, discuss recent clinical experience with Listeria-based immunotherapies, and detail the advancements in development of improved Listeria-based vaccine platforms and in their utilization.